Mara, daughter of the Nile - McGraw, Eloise Jarvis (New York : Puffin Books, 1985)
The adventures of an ingenious Egyptian slave girl who undertakes a dangerous assignment as a spy in the royal palace of Thebes, in the days when Queen Hatshepsut ruled.
Horn Book
6.0
5-8.
5-8
Keywords: Historical fiction; Spies -- Fiction; Historical fiction; Spies -- Fiction; Egypt -- History -- To 332 B.C -- Fiction; Thebes (Egypt : Extinct city) -- Fiction; Egypt -- Antiquities -- Fiction; Thebes (Egypt : Extinct city) -- Fiction